Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula - Schram, Julie B; Schoenrock, Kathryn M; McClintock, James B; Amsler, Charles D; Angus, Robert A (Polar Research, 2015)
Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012–May 2013), daily schedule over three months (March–May 2013) and semidiurnal schedule over five weeks (March–April 2013). A notable pH increase (max pH = 8.62) occurred in the late austral spring/summer (November–December 2012), coinciding with sea-ice break-out and subsequent increase in primary productivity. We detected semidiurnal variation in seawater pH with a maximum variation of 0.13 pH units during the day and 0.11 pH units during the night. Daily variation in pH is likely related to biological activity, consistent with previous research. We calculated the variation in dissolved inorganic carbon (DIC) over each seawater measurement frequency, focusing on the primary DIC drivers in the Palmer Station region. From this, we estimated net biological activity and found it accounts for the greatest variations in DIC. Our seasonal data suggest that this coastal region tends to act as a carbon dioxide source during austral winter months and as a strong sink during the summer. These data characterize present-day seawater carbonate chemistry and the extent to which these measures vary over multiple time scales. This information will inform future experiments designed to evaluate the vulnerability of coastal benthic Antarctic marine organisms to ocean acidification. Keywords: Antarctica; aragonite; calcite; pH; seawater chemistry; total alkalinity.
Keywords: Sørishavet; analyser; havis; kjemisk; sjøis; sjøvann

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

Standardized algal growth potential and/or algal primary production rates of maritime Antarctic stream waters (King George Island, South Shetlands) - Kvíderová, Jana; Elster, Josef (Polar Research, 2013)
In addition to the chemical analyses providing total nutrient content, standardized water trophic status bioassays are useful in the determination of available nutrients for primary producers. The aim of the study was to determine the standardized values of algal growth potential (AGP) and algal primary productivity rate (APPR) of maritime Antarctic stream water using modified AGP/APPR protocols. The standardized values of AGP and the APPR of oligotrophic and mesotrophic water samples from snow-melt streams were measured, and possible nutrient limitation and heavy metal inhibition were evaluated at 5°C and 25°C using polar and temperate strains of Stichococcus bacillaris, respectively. The water samples were enriched for the nutrient limitation tests with 1000 mμ l-1 NO3- -N, 50 μg l-1 PO43- -P, and a mixture of 1000 μg l-1 NO3- -N + 50 μg l-1 PO43- -P, and for the heavy metal inhibition tests with 1000 mg l-1 Na2-ethylenediaminetetraacetic acid (EDTA). The AGP of oligotrophic samples was significantly lower than that of the mesotrophic ones at both temperatures. In addition, AGP was significantly higher at 5°C than at 25°C. Oligotrophic samples were identified as being nitrogen limited, while no nutrient limitation was observed in the mesotrophic samples. No statistically significant heavy metal inhibition was observed at either temperature. The positive correlation of AGP and water nutrient content indicates that the method used accurately and comprehensively monitors the changes in biological availability of mineral nutrients and can provide a standardized reference point for similar exploration of freshwater ecosystems across both polar regions. Keywords: Maritime Antarctic; microalgae; nutrient limitations; snow-melt stream water.
Keywords: Antarktis; alger; analyser; ferskvann; innsjø; kjemisk; klimaendringer; næringsstoff; polarområdene; snø; strøm; økosystemer

Effect of isolation temperature on the characteristics of extracellular proteases produced by Antarctic bacteria - Vazquez, Susana C; Mac Cormack, Walter P (Polar Research, 2002)
Protease-producing psychrotolerant bacteria were isolated from Antarctic biotopes on casein agar plates using different incubation temperatures. Most of the isolates were non-spore-forming Gram-negative motile rods with catalase activity, 30% were pigmented and none of them were glucose fermenters. All the strains were grown in liquid cultures at 20°C and protease secretion was tested using the azocasein method. Despite their capacity for production of a clear zone of hydrolysis in agar plates, some strains did not produce detectable levels of proteolytic activity in liquid cultures. The lowest apparent optimum temperature for protease activity found in culture supernatants was 40°C. Almost all the strains showed activation energy values about 10-20 kJ-mol?1 lower than that observed for a mesophilic Subtilisin. Most of the proteases showed optimal activity at neutral or alkaline pH values and developed a multiple-band profile on gelatine-SDS-PAGE. It was observed that the lower the strain isolation temperature was, the more stongly cold-adapted–in terms of optimal temperature and activation energy–were the proteases produced by them. This dependence of the characteristics of the proteases on the isolation temperature is an important factor to take into account in the design of screening programmes directed towards the isolation of psychrotolerant bacteria able to produce proteases strongly or weakly adapted to work in the cold. The Antarctic area explored proved to be a promising source of proteolytic bacteria with potential use in industrial processes to be carried out at low or moderate temperatures.
Keywords: Antarktis; analyser; bakterier; ekspedisjoner; mikrobiologi

Excess and deficit of sulfate in polar snow - Gjessing, Yngvar (Atmospheric Environment (1967), 1989)
Keywords: Antarktis; analyser; kjemisk; meteorologi; sjøvann; snø

The filtering effect of snow - Gjessing, Yngvar (International Association of Hydrological Sciences Publication, 1977)
Keywords: Dronning Maud Land; analyser; hydrologi; is; kjemisk; snø